Early presenting hypertrophic pyloric stenosis with transient antroduodenal dysmotility in a preterm neonate: A case report - Sang-won Cho; Eun Sun Kim; Suk-Bae Moon (Elsevier, 2015)
Hypertrophic pyloric stenosis (HPS) is one of the most common gastrointestinal disorders that require surgical intervention in early infancy. Clinical presentation, diagnosis, and treatment have been well established in typical cases. We herein describe an unusual case of early presenting HPS with transient postoperative feeding intolerance after complete myotomy in a preterm newborn. An ex-31-week preterm newborn (birth weight, 1760 g) with persistent feeding intolerance since the first feeding was referred for surgery on the 7th day of life. Abdominal ultrasonography (USG) revealed an elongated pyloric channel (11 mm) with thickened pyloric muscle (2.1 mm). Laparotomy was performed and confirmed suspected HPS. Pylomyotomy was successful, but feeding intolerance persisted until postoperative day 12. USG on postoperative day 12 noted antroduodenal dysmotility, and transpyloric tube feeding was started. Full feeds were reached 8 days after tube feeding, which was then converted to full oral feeding. HPS should be considered in patients who show feeding intolerance shortly after birth. USG criteria for HPS in preterm infants has not yet been established. Transient antroduodenal dysmotility could be a reason for persistent feeding intolerance after complete myotomy in preterm infants, and transpyloric tube feeding could be a treatment in such cases.